Malignant liver tumors : current and emerging therapies - Belghiti, J. [ (Jacques)]; Breitenstein, Stefan; Clavien, Pierre-Alain (Wiley-Blackwell, 2010)
Presents a comprehensive of the established treatment modalities for malignant liver tumors that helps you sort through the proliferation of competitive approaches and choose the best treatment options for your patient.